(untitled) (Economics and region, 2020)
The article considers the dynamics of prices for futures contracts in the sugar market, in particular-two («Sugar No. 11 Futures», «Sugar No. 16 Futures») on the Intercontinental Commodity Exchange – ICE; one («White Sugar Futures (No. 407)») on the London International Financial Futures and Options Exchange – Liffe (LIFFE); one («Sugar White») on the Zhengzhou Commodity Exchange – ZCE. In this article, in order to forecast the price of sugar on London intercontinental financial futures and options exchange – Liffe. Correlation and regression analysis is applied and the main stages of building a multiple linear correlation and regression model are presented. The dynamics of the average annual value of the White Sugar Futures contract (No. 407) is given. The Fisher F-test was used for rapid diagnostics of the adequacy of the multiple correlation-regression model.